PHOTOVOLTAIC SYSTEM FOR POWERING A REMOTE ACTUATION SYSTEM - Rádoi, Radu; Dumitrescu, Liliana; Tudor, Bogdan; Benescu, Andrei; Blejan, Robert (International Multidisciplinary Scientific GeoConference SGEM, 2024)
In isolated areas without access to the grid where it is necessary to operate certain equipment, such as the operation of a valve in a mining area or some gates on a irrigation canals, an installation with fotovoltaic supply can be used. Considering the intermittent operation regime of the driven equipment, a solar-powered drive installation can be designed, and by storing the energy in a battery, operation can be ensured during the night as well. Thus, the PV power system must be sized (PV peak power, battery and inverter capacities) so as to support the power of a compact hydraulic power pack and accessory equipment. In order not to be damaged by the weather conditions, the equipment must be housed in a water-resistant enclosure The system must also be equipped with an energy management unit and remote control (GSM or LoRa Gateway). The article presents the realization of such a system and the tests carried out to monitor the production and consumption of electricity during several operating cycles.